Large-dosage fly ash-based artificial aggregate and method for preparing water permeable brick by using same

By controlling the water-cement ratio and using polycarboxylic acid-based water reducing agent, the strength of large-scale fly ash-based artificial aggregate is significantly improved, and the performance of permeable bricks is improved through the fly ash buffer layer, which solves the problems of low fly ash utilization rate and insufficient permeable brick performance in the prior art, and achieves efficient and environmentally friendly fly ash resource utilization and the preparation of high-performance permeable bricks.

CN119912214APending Publication Date: 2025-05-02SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411946047.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing fly ash resource utilization technology has problems such as high energy consumption, high cost, high pollution, limited fly ash dosage, low strength, complex process, and low production efficiency, making it difficult to meet the needs of high-performance permeable bricks and high-strength aggregates.

Method used

By controlling the use of low water-cement ratio (0.18-0.22) and polycarboxylic acid-based water reducing agent, the fluidity of the mixture is regulated, and the strength of large-scale fly ash-based artificial aggregate is significantly improved. By spraying fly ash on the surface of the artificial aggregate to form a "fly ash buffer layer", the contact interface between the aggregate and cement base is improved and the bonding strength is enhanced.

Benefits of technology

It has achieved efficient utilization of high-volume fly ash, significantly improved the strength, durability and wear resistance of permeable bricks, met the demand for high-performance permeable bricks in sponge urban construction and green buildings, and has significant economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a large-volume fly ash-based artificial aggregate and a method for preparing a water permeable brick by using the same. According to the invention, by controlling the use of a low water cement ratio (0.18-0.22) and a polycarboxylic acid water reducer and regulating and controlling the flowability of a mixture, the compressive strength (more than 60MPa) of the artificial aggregate is remarkably improved, and by spraying fly ash on the surface of the artificial aggregate to form a fly ash buffer layer, the strength, durability and wear resistance of the water permeable brick are remarkably improved; the fine particles of the fly ash fill gaps between the artificial aggregate and the cement-based slurry in the pressing process, the overall compactness of the mixture is enhanced, a compact protection layer is formed on the surface of the water permeable brick, the compressive strength and the wear resistance of the water permeable brick are effectively improved, meanwhile, the resource utilization rate of the fly ash is greatly increased, and the production cost is reduced. The problem of high-efficiency utilization of high-volume fly ash in the water permeable brick is solved, and the method has remarkable economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material preparation, and in particular to a large-volume fly ash-based artificial aggregate and a method for preparing permeable bricks using the same. Background Art

[0002] Although fly ash has been used in some building materials fields, its utilization rate is still low. In addition, due to the sluggish building materials market in recent years, the market demand for fly ash has continued to decline, and even in some areas, there has been a significant phenomenon of sluggish sales, which has further aggravated the problem of fly ash disposal. At the same time, the society's demand for high-performance and environmentally friendly building materials is growing, especially the construction of sponge cities has put forward higher requirements for high-permeability and high-strength permeable bricks. The green building field also has an urgent need for lightweight, high-strength, energy-saving and environmentally friendly aggregate materials. However, there are many bottlenecks in the existing fly ash resource utilization technology: the traditional sintering method for preparing permeable bricks has high energy consumption, high cost and high pollution; although the process of concrete permeable bricks with cement as the main binder is simple, the fly ash content is limited (generally less than 50%), making it difficult to achieve large-scale and efficient utilization of fly ash; the existing fly ash-based artificial aggregate preparation methods generally have problems such as low strength (generally less than 60MPa), complex process flow and low production efficiency, which makes it difficult to meet the market's growing demand for high-performance building materials.

[0003] In addition, among the existing methods for preparing permeable bricks, although some attempts have been made to improve the performance of permeable bricks through surface coatings or additives, these methods often have limited effects and it is difficult to simultaneously take into account high strength, high permeability and low cost. For example: the use of organic coatings is costly and has poor durability; the addition of inorganic materials will reduce permeability, etc. In particular, the technical difficulties in preparing permeable bricks with both high strength and high permeability at high fly ash dosages have not been effectively solved. Therefore, there is an urgent need for a new preparation method that can break through the bottleneck of existing technologies, achieve efficient utilization of high-dosage fly ash, and simultaneously prepare high-performance permeable bricks and high-strength aggregates, so as to solve the environmental problems of fly ash, promote resource recycling, and promote the development of green buildings. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing permeable bricks with a large amount of fly ash-based artificial aggregate, which not only realizes the preparation of permeable bricks with both high strength and high permeability, but also greatly improves its wear resistance and durability. The method for preparing permeable bricks of the present invention firstly controls the low water-cement ratio (0.18-0.22) and the use of polycarboxylic acid-based water reducer to regulate the fluidity of the mixture, significantly improves the strength of the large amount of fly ash-based artificial aggregate (compressive strength exceeds 60MPa), and forms a "fly ash buffer layer" by spraying fly ash on the surface of the artificial aggregate. The fly ash buffer layer is used to improve the contact interface between the aggregate and the cement-based material, and enhance the bonding strength between the aggregates; and significantly improves the strength, durability and wear resistance of the permeable brick. The fine particles of fly ash fill the gaps between the artificial aggregate and the cement-based slurry during the pressing process, enhance the overall density of the mixture, especially form a dense protective layer on the surface of the permeable brick, effectively improving the compressive strength and wear resistance of the permeable brick. This protective layer can prevent the surface from becoming loose or cracked, significantly increasing the service life of the permeable brick.

[0005] Another object of the present invention is to provide a large amount of fly ash-based artificial aggregate, the preparation process of which controls the low water-cement ratio (0.18-0.22) and the use of a polycarboxylic acid-based water reducer to regulate the fluidity of the mixture, thereby significantly improving the strength of the large amount of fly ash-based artificial aggregate (compressive strength exceeds 60MPa).

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing permeable bricks using a large amount of fly ash-based artificial aggregate, comprising the following steps:

[0008] (1) Preparation of large amount of fly ash-based artificial aggregate:

[0009] (1-1) mixing fly ash and cement according to a weight ratio to obtain a first mixture, wherein the fly ash content is 70-90% and the cement content is 10-30%;

[0010] (1-2) adding water and a polycarboxylic acid-based water reducer to the first mixture obtained in step (1-1), wherein the water-cement ratio is 0.18-0.22, and the amount of the polycarboxylic acid-based water reducer is 0.5%-2% of the total mass of fly ash and cement; stirring the mixture for 3-10 minutes using a mixer to prepare a uniform slurry;

[0011] (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense;

[0012] (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used;

[0013] (1-5) Processing: After the curing is completed, the solidified body is crushed and sieved by a screening device to obtain a large amount of fly ash-based artificial aggregate with a particle size of 2-5 mm and 5-10 mm;

[0014] (2) Mixing: mixing the large-volume fly ash-based artificial aggregate prepared in step (1) with the cement-based slurry at a mass ratio of 4:1-6:1 and stirring evenly until all surfaces of the large-volume fly ash-based artificial aggregate are coated with a layer of cement-based slurry to obtain a second mixture;

[0015] (3) Surface treatment: Spray fly ash on the surface of the second mixture obtained in step (2), with the spraying amount being 1% to 3% of the total mass of the cement-based slurry and the artificial aggregate, and continue stirring to make the fly ash evenly coated on the surface of the artificial aggregate coated with the cement-based slurry to form a fly ash buffer layer, thereby obtaining a mixture;

[0016] (4) Molding: Filling the mixture obtained in step (3) into a mold, applying a pressure of 5-10 MPa to press and mold to obtain a brick;

[0017] (5) Curing: Curing the brick blank obtained in step (4) to obtain a permeable brick.

[0018] Preferably, the curing in steps (1-4) is specifically:

[0019] The steam curing temperature is 70-100℃ and the time is 24-48 hours; the autoclave curing pressure is 0.6-1.0MPa and the time is 6-10 hours;

[0020] The maintenance described in step (5) is specifically:

[0021] The curing method is steam curing or autoclave curing. The steam curing temperature is 70-100°C and the time is 24-48 hours; the autoclave curing pressure is 0.6-1.0MPa and the time is 6-10 hours.

[0022] Preferably, in parts by weight, the cement-based slurry in step (2) comprises 50-60 parts of cement, 40-50 parts of fly ash, and 1-5 parts of silica fume; the cement-based slurry also comprises a water reducer, and the fluidity of the mud-based slurry is regulated by the water reducer to 180-220 mm.

[0023] Preferably, the high-volume fly ash-based artificial aggregate in step (2) is prepared by mixing high-volume fly ash-based artificial aggregate with a particle size of 2-5 mm and high-volume fly ash-based artificial aggregate with a particle size of 5-10 mm in a mass ratio of 8:2 to 2:8.

[0024] Preferably, the fly ash sprayed in step (3) fills the gap between the artificial aggregate and the cement base material, and is used to enhance the overall density of the permeable brick and improve the compressive strength, wear resistance and durability of the permeable brick.

[0025] Preferably, the compressive strength of the permeable brick is greater than 30 MPa and the water permeability coefficient is greater than 2×10 -2 cm / s, grinding pit length is less than 28mm.

[0026] The present invention also provides a large amount of fly ash-based artificial aggregate, which is prepared by the following method:

[0027] (1-1) mixing fly ash and cement according to a weight ratio to obtain a first mixture, wherein the fly ash content is 70-90% and the cement content is 10-30%;

[0028] (1-2) adding water and a polycarboxylic acid-based water reducer to the first mixture obtained in step (1-1), wherein the water-cement ratio is 0.18-0.22, and the amount of the polycarboxylic acid-based water reducer is 0.5%-2% of the total mass of fly ash and cement; stirring the mixture for 3-10 minutes using a mixer to prepare a uniform slurry;

[0029] (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense;

[0030] (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used;

[0031] (1-5) Processing: After curing, the solidified body is crushed and sieved by screening equipment to obtain large-volume fly ash-based artificial aggregate with particle sizes of 2-5 mm and 5-10 mm.

[0032] Preferably, the water reduction rate of the polycarboxylic acid-based water reducer is ≥25%, and the solid content is ≥10%.

[0033] Preferably, the fluidity of the slurry in step (1-2) is 160-200 mm.

[0034] Preferably, the compressive strength of the high-dosage fly ash-based artificial bone is greater than 60 MPa, and the test method is:

[0035] The slurry prepared in step (1-2) was molded into a cubic test block of 10 cm×10 cm×10 cm, and after curing according to step (1-4), its compressive strength was tested.

[0036] Preferably, the cement is ordinary Portland cement with a strength grade of ≥42.5; the fly ash activity index is >70%, the particle size is 25-300 μm, and the aluminum oxide content is ≥30%; the polycarboxylic acid-based water reducer has a water reduction rate of ≥25% and a solid content of ≥10%.

[0037] The present invention provides an efficient, environmentally friendly and economical way to utilize fly ash resources, and prepares artificial aggregate and permeable bricks with superior performance. It has significant innovation in improving the strength, wear resistance and durability of permeable bricks, and has significant social and economic benefits. Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0038] (1) Production of high-performance permeable bricks: The permeable bricks produced by using the fly ash-based artificial aggregate with a large amount of content prepared by the present invention have both high strength and high permeability, meeting the demand for high-performance permeable bricks in sponge city construction and green buildings, and are significantly better than the high energy consumption and high pollution of traditional sintered permeable bricks and the low strength and low fly ash content of concrete permeable bricks with cement as the main binder.

[0039] (2) Significantly improve the utilization rate of fly ash: The present invention adopts a high amount of fly ash (70-90%), which greatly improves the utilization rate of fly ash, effectively solves the problems of fly ash storage and environmental pollution, and realizes the efficient and high-value utilization of fly ash. This has significant advantages compared with the limited amount of fly ash in the prior art.

[0040] (3) Preparation of high-strength artificial aggregate: The artificial aggregate prepared by the present invention has high compressive strength (>60MPa), which is much higher than the strength of existing fly ash aggregate, meets the demand for high-performance building materials, and can be widely used in various engineering constructions.

[0041] (4) Simplified process flow and improved production efficiency: The process flow of the present invention is relatively simple and has high production efficiency, which reduces production costs and improves economic benefits. This is in sharp contrast to the current situation of complex and inefficient fly ash aggregate preparation technology.

[0042] (5) Significant environmental benefits: The present invention utilizes a large amount of fly ash, reduces environmental pollution, reduces the occupation of land resources, and has significant environmental benefits. DETAILED DESCRIPTION

[0043] In order to more clearly illustrate the technical solution of the present invention, several specific embodiments are provided below. It should be particularly pointed out that these embodiments are only used for illustration and are not intended to limit the scope of protection of the present invention. Any equivalent solution obtained by conventional technical means based on the concept of the present invention belongs to the scope of protection of the present invention.

[0044] In the following embodiments, the cement is ordinary Portland cement with a strength grade of ≥42.5; the fly ash activity index is >70%, the particle size is 25-300 μm, and the aluminum oxide content is ≥30%; the polycarboxylic acid-based water reducer has a water reduction rate of ≥25% and a solid content of ≥10%.

[0045] Example 1

[0046] The present embodiment provides a method for preparing a permeable brick using a large amount of fly ash-based artificial aggregate and using the same, comprising the following steps:

[0047] (1) Preparation of fly ash-based artificial aggregate

[0048] Fly ash and cement are mixed in a mass ratio of 80:20. After mixing evenly, water is added at a water-cement ratio of 0.20, and then polycarboxylic acid water reducer is added at 0.8% of the total mass of fly ash and cement. The mixture is stirred for 5 minutes using a mixer to prepare a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, three 10cm×10cm×10cm specimens are formed to test the compressive strength. After the slurry is initially set, the tray is placed in a steam curing box at a temperature of 80°C and steamed for 24 hours. After the steam curing is completed, the solidified body is crushed with a crusher and sieved by a screening device to obtain fly ash-based artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm specimen is 63.5MPa.

[0049] (2) Preparation of permeable bricks using artificial aggregates

[0050] Cement, fly ash and silica fume are mixed in a mass ratio of 55:42:3, water is added in a water-cement ratio of 0.18, and then a polycarboxylate water reducer is added in a ratio of 0.8% of the total mass of cement, fly ash and silica fume, and stirred by a mixer to prepare a slurry with a flow rate of 200 mm; fly ash-based artificial aggregates with particle sizes of 2-5 mm and 5-10 mm obtained in the above (1) are mixed in a mass ratio of 8:2, and then gradually added to the slurry and stirred evenly, with the mass ratio of artificial aggregate to slurry being 4:1, until all artificial aggregate surfaces are coated with a layer of cement-based slurry; fly ash is sprayed on the surface of the obtained mixture, and stirring is continued to make the fly ash evenly coated on the surface of the artificial aggregate coated with the cement-based slurry to prepare a mixture, and the mass of the sprayed fly ash is 2% of the total mass of the cement-based slurry and the fly ash-based artificial aggregate; and a fly ash buffer layer is formed. The obtained mixture was filled into a mold and pressed under a pressure of 8 MPa to obtain a brick blank. The obtained brick blank was steam cured at a temperature of 80°C for 24 hours. Finally, a high-dosage fly ash-based permeable brick was obtained. The relevant performance indicators of the product are shown in Table 1.

[0051] Example 2

[0052] The present embodiment provides a method for preparing permeable bricks using a large amount of fly ash-based artificial aggregate and using the same, comprising the following steps:

[0053] (1) Preparation of fly ash-based artificial aggregate

[0054] Fly ash and cement are mixed in a mass ratio of 75:25. After mixing evenly, water is added at a water-cement ratio of 0.18, and then polycarboxylic acid water reducer is added at 1.2% of the total mass of fly ash and cement. The mixture is stirred for 5 minutes using a mixer to prepare a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, three 10cm×10cm×10cm specimens are formed to test the compressive strength. After the slurry is initially set, the tray is placed in a steam curing box at a temperature of 90°C and steamed for 48 hours. After the steam curing is completed, the solidified body is crushed with a crusher and sieved by a screening device to obtain fly ash-based artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm specimen is 71.2MPa.

[0055] (2) Preparation of permeable bricks using artificial aggregates

[0056] Cement, fly ash and silica fume are mixed in a mass ratio of 55:40:5, water is added in a water-cement ratio of 0.22, and then a polycarboxylate water reducer is added in a mass ratio of 0.9% of the total mass of cement, fly ash and silica fume, and stirred with a mixer to prepare a slurry with a flow rate of 218 mm; fly ash-based artificial aggregates with particle sizes of 2-5 mm and 5-10 mm obtained in the above (1) are mixed in a mass ratio of 6:4, and then gradually added to the slurry and stirred evenly, the mass ratio of artificial aggregate to slurry is 6:1, until all artificial aggregate surfaces are coated with a layer of cement-based slurry; fly ash is sprayed on the surface of the obtained mixture, and stirring is continued to make the fly ash evenly coated on the surface of the artificial aggregate coated with the cement-based slurry to prepare a mixture, the mass of the fly ash sprayed is 2% of the total mass of the cement-based slurry and the fly ash-based artificial aggregate, and stirring is uniform to form a fly ash buffer layer. The obtained mixture was filled into a mold and pressed under a pressure of 8 MPa to obtain a brick blank; the obtained brick blank was autoclaved at a pressure of 0.8 MPa for 8 hours. Finally, a high-dosage fly ash-based permeable brick was obtained, and the relevant performance indicators of the product are shown in Table 1.

[0057] Example 3

[0058] The present embodiment provides a method for preparing a permeable brick using a large amount of fly ash-based artificial aggregate and using the same, comprising the following steps:

[0059] (1) Preparation of fly ash-based artificial aggregate

[0060] Fly ash and cement are mixed in a mass ratio of 85:15. After mixing evenly, water is added at a water-cement ratio of 0.16, and then polycarboxylic acid water reducer is added at 1.3% of the total mass of fly ash and cement. The mixture is stirred for 5 minutes using a mixer to prepare a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, three 10cm×10cm×10cm specimens are formed to test the compressive strength. After the slurry is initially set, the tray is placed in an autoclave for curing at a pressure of 1.0MPa for 10 hours. After the autoclave is completed, the solidified body is crushed with a crusher and sieved by a screening device to obtain fly ash-based artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm specimen is 73.8MPa.

[0061] (2) Preparation of permeable bricks using artificial aggregates

[0062] Cement, fly ash and silica fume are mixed in a mass ratio of 60:35:5, water is added in a water-cement ratio of 0.18, and then a polycarboxylate water reducer is added in a ratio of 1% of the total mass of cement, fly ash and silica fume, and stirred with a mixer to prepare a slurry with a flow rate of 205 mm; fly ash-based artificial aggregates with particle sizes of 2-5 mm and 5-10 mm obtained in the above (1) are mixed in a mass ratio of 5:5, and then gradually added to the slurry and stirred evenly. The mass ratio of artificial aggregate to slurry is 5: 1, until all artificial aggregate surfaces are coated with a layer of cement-based slurry; spray fly ash on the surface of the obtained mixture, continue to stir, so that the fly ash is evenly coated on the surface of the artificial aggregate coated with cement-based slurry, prepare a mixture, the mass of the sprayed fly ash is 1% of the total mass of the cement-based slurry and fly ash-based artificial aggregate; fill the obtained mixture into a mold, apply a pressure of 10MPa to press and form, and obtain a brick; the obtained brick is steam-cured at a temperature of 80°C for 36 hours. Finally, a high-dosage fly ash-based permeable brick is obtained, and the relevant performance indicators of the product are shown in Table 1.

[0063] Example 4

[0064] The present embodiment provides a method for preparing a permeable brick using a large amount of fly ash-based artificial aggregate and using the same, comprising the following steps:

[0065] (1) Preparation of fly ash-based artificial aggregate

[0066] Fly ash and cement are mixed in a mass ratio of 80:20. After mixing evenly, water is added at a water-cement ratio of 0.19, and then polycarboxylic acid water reducer is added at 1.2% of the total mass of fly ash and cement. The mixture is stirred for 5 minutes using a mixer to prepare a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, three 10cm×10cm×10cm specimens are formed to test the compressive strength. After the slurry is initially set, the tray is placed in a steam curing box at a temperature of 80°C and steamed for 24 hours. After the steam curing is completed, the solidified body is crushed with a crusher and sieved by a screening device to obtain fly ash-based artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm specimen is 66MPa.

[0067] (2) Preparation of permeable bricks using artificial aggregates

[0068] Cement, fly ash and silica fume are mixed in a mass ratio of 55:40:5, water is added in a water-cement ratio of 0.20, and then polycarboxylate water reducer is added in a ratio of 0.8% of the total mass of cement, fly ash and silica fume, and stirred with a mixer to prepare a slurry with a flow rate of 200 mm; fly ash-based artificial aggregates with particle sizes of 2-5 mm and 5-10 mm obtained in (1) are mixed in a mass ratio of 4:6, and then gradually added to the slurry and stirred evenly. The mass ratio of artificial aggregate to slurry is 5. 5:1, until all the artificial aggregate surfaces are covered with a layer of cement-based slurry; spray fly ash on the surface of the obtained mixture, continue to stir, so that the fly ash is evenly coated on the surface of the artificial aggregate coated with cement-based slurry, prepare a mixture, the mass of fly ash sprayed is 1.5% of the total mass of cement-based slurry and fly ash-based artificial aggregate; fill the obtained mixture into a mold, apply a pressure of 9MPa to press and form, and obtain a brick; the obtained brick is autoclaved and cured at a pressure of 0.9MPa for 7 hours. Finally, a high-dosage fly ash-based permeable brick is obtained, and the relevant performance indicators of the product are shown in Table 1.

[0069] Comparative Example 1: Using natural aggregate to prepare permeable bricks without surface treatment of aggregate

[0070] Cement, fly ash and silica fume are mixed evenly at a mass ratio of 55:40:5, water is added at a water-cement ratio of 0.20, and then polycarboxylic acid water reducer is added at 0.8% of the total mass of cement, fly ash and silica fume, and stirred with a mixer to prepare a slurry with a flow of 200mm; 2-5mm and 5-10mm natural aggregates are mixed at a mass ratio of 8:2, and then gradually added to the slurry, stirred evenly, and the mass ratio of aggregate to slurry is 5:1, until the slurry completely wraps the artificial aggregate; the obtained mixture is filled into a mold, and a pressure of 9MPa is applied to press and form to obtain a brick; the obtained brick is autoclaved and cured at a pressure of 0.9MPa for 7 hours. The relevant performance indicators of the permeable bricks are shown in Table 1.

[0071] Comparative Example 2: No surface treatment of aggregate

[0072] A method for preparing permeable bricks using a large amount of fly ash-based artificial aggregate and using the same comprises the following steps:

[0073] (1) Preparation of fly ash-based artificial aggregate

[0074] Fly ash and cement are mixed in a mass ratio of 80:20. After mixing evenly, water is added at a water-cement ratio of 0.19, and then polycarboxylic acid water reducer is added at 1.2% of the total mass of fly ash and cement. The mixture is stirred for 5 minutes using a mixer to prepare a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, three 10cm×10cm×10cm specimens are formed to test the compressive strength. After the slurry is initially set, the tray is placed in a steam curing box at a temperature of 80°C and steamed for 24 hours. After the steam curing is completed, the solidified body is crushed with a crusher and sieved by a screening device to obtain fly ash-based artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm specimen is 66MPa.

[0075] (2) Preparation of permeable bricks using artificial aggregates

[0076] Cement, fly ash and silica fume are mixed evenly in a mass ratio of 55:40:5, water is added at a water-cement ratio of 0.20, and then polycarboxylic acid water reducer is added at 0.8% of the total mass of cement, fly ash and silica fume, and stirred with a mixer to prepare a slurry with a flow rate of 200 mm; the fly ash-based artificial aggregates with particle sizes of 2-5 mm and 5-10 mm obtained in the above (1) are mixed in a mass ratio of 4:6, and then gradually added to the slurry, stirred evenly, and the mass ratio of artificial aggregate to slurry is 5.5:1, until the slurry completely covers the artificial aggregate; the obtained mixture is filled into a mold, and a pressure of 9 MPa is applied to press and form to obtain a brick; the obtained brick is autoclaved and cured at a pressure of 0.9 MPa for 7 hours. Finally, a high-dosage fly ash-based permeable brick is obtained, and the relevant performance indicators of the product are shown in Table 1.

[0077] Table 1 Performance indicators of prepared permeable bricks

[0078] Example Compressive strength(MPa) <![CDATA[Coefficient of permeability (×10 -2 cm / s)]]> Grinding pit length (mm) Example 1 32.3 2.46 25.5 Example 2 30.8 2.32 25.9 Example 3 35.6 2.15 26.7 Example 4 33.4 2.26 26.3 Comparative Example 1 32.5 2.24 33.2 Comparative Example 2 29.7 2.19 35.8

[0079] The present invention controls the fluidity of the mixture by controlling the low water-cement ratio (0.18-0.22) and the use of polycarboxylic acid-based water reducers, significantly improves the strength of the aggregate (compressive strength exceeds 60MPa), and forms a "fly ash buffer layer" by spraying fly ash on the surface of the aggregate, which significantly improves the strength, durability and wear resistance of the permeable brick. The fine particles of fly ash fill the gaps between the artificial aggregate and the cement-based slurry during the pressing process, enhance the overall density of the mixture, and especially form a dense protective layer on the surface of the permeable brick, which effectively improves the compressive strength and wear resistance of the permeable brick. This protective layer can prevent the surface from becoming loose or cracked, and significantly improves the service life of the permeable brick. Through the technical solution of the invention, the resource utilization rate of fly ash is greatly improved, the problem of efficient utilization of high-dosage fly ash in permeable bricks is solved, and the demand for high-performance permeable bricks in sponge city construction is met, which has significant economic and environmental benefits.

[0080] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing permeable bricks using a large amount of fly ash-based artificial aggregate, characterized in that: The following steps are involved: (1) Preparation of large amount of fly ash-based artificial aggregate: (1-1) mixing fly ash and cement according to a weight ratio to obtain a first mixture, wherein the fly ash content is 70-90% and the cement content is 10-30%; (1-2) adding water and a polycarboxylic acid-based water reducer to the first mixture obtained in step (1-1), wherein the water-cement ratio is 0.18-0.22, and the amount of the polycarboxylic acid-based water reducer is 0.5%-2% of the total mass of fly ash and cement; stirring the mixture for 3-10 minutes using a mixer to prepare a uniform slurry; (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense; (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used; (1-5) Processing: After the curing is completed, the solidified body is crushed and sieved by a screening device to obtain a large amount of fly ash-based artificial aggregate with a particle size of 2-5 mm and 5-10 mm; (2) Mixing: mixing the large-volume fly ash-based artificial aggregate prepared in step (1) with the cement-based slurry at a mass ratio of 4:1-6:1 and stirring evenly until all surfaces of the large-volume fly ash-based artificial aggregate are coated with a layer of cement-based slurry to obtain a second mixture; (3) Surface treatment: Spray fly ash on the surface of the second mixture obtained in step (2), with the spraying amount being 1% to 3% of the total mass of the cement-based slurry and the artificial aggregate, and continue stirring to make the fly ash evenly coated on the surface of the artificial aggregate coated with the cement-based slurry to form a fly ash buffer layer, thereby obtaining a mixture; (4) Molding: Filling the mixture obtained in step (3) into a mold, applying a pressure of 5-10 MPa to press and mold to obtain a brick; (5) Curing: Curing the bricks obtained in step (4) to obtain permeable bricks.

2. The method for preparing permeable bricks using a large amount of fly ash-based artificial aggregate according to claim 1, characterized in that: The maintenance described in steps (1-4) is specifically: The steam curing temperature is 70-100℃ and the time is 24-48 hours; the autoclave curing pressure is 0.6-1.0MPa and the time is 6-10 hours; The maintenance described in step (5) is specifically: The curing method is steam curing or autoclave curing. The steam curing temperature is 70-100°C and the time is 24-48 hours; the autoclave curing pressure is 0.6-1.0MPa and the time is 6-10 hours.

3. The method for preparing permeable bricks using fly ash-based artificial aggregate with a large amount of addition according to claim 1, characterized in that: In parts by weight, the cement-based slurry in step (2) comprises 50-60 parts of cement, 40-50 parts of fly ash, and 1-5 parts of silica fume; the cement-based slurry also comprises a water reducer, and the fluidity of the mud-based slurry is regulated to 180-220 mm by the water reducer.

4. The method for preparing permeable bricks using fly ash-based artificial aggregate with a large amount of blending according to claim 1, characterized in that: The high-volume fly ash-based artificial aggregate in step (2) is prepared by mixing high-volume fly ash-based artificial aggregate with a particle size of 2-5 mm and high-volume fly ash-based artificial aggregate with a particle size of 5-10 mm in a mass ratio of 8:2 to 2:

8.

5. The method for preparing permeable bricks using fly ash-based artificial aggregate with a large amount of addition according to claim 1, characterized in that: The fly ash sprayed in step (3) fills the gap between the artificial aggregate and the cement base material, and is used to enhance the overall density of the permeable brick and improve the compressive strength, wear resistance and durability of the permeable brick.

6. The method for preparing permeable bricks using fly ash-based artificial aggregate with a large amount of addition according to claim 1, characterized in that: The compressive strength of the permeable brick is greater than 30MPa and the water permeability coefficient is greater than 2×10 -2 cm / s, grinding pit length is less than 28mm.

7. A large amount of fly ash-based artificial aggregate, characterized in that: Prepared by the following method: (1-1) mixing fly ash and cement according to a weight ratio to obtain a first mixture, wherein the fly ash content is 70-90% and the cement content is 10-30%; (1-2) adding water and a polycarboxylic acid-based water reducer to the first mixture obtained in step (1-1), wherein the water-cement ratio is 0.18-0.22, and the amount of the polycarboxylic acid-based water reducer is 0.5%-2% of the total mass of fly ash and cement; stirring the mixture for 3-10 minutes using a mixer to prepare a uniform slurry; (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense; (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used; (1-5) Processing: After curing, the solidified body is crushed and sieved by screening equipment to obtain large-volume fly ash-based artificial aggregate with particle sizes of 2-5 mm and 5-10 mm.

8. The fly ash-based artificial aggregate with a large amount of addition according to claim 7, characterized in that: The water reduction rate of the polycarboxylic acid-based water reducer is ≥25%, and the solid content is ≥10%.

9. The fly ash-based artificial aggregate with a large amount of addition according to claim 8, characterized in that: The fluidity of the slurry in step (1-2) is 160-200 mm.

10. The fly ash-based artificial aggregate with a large amount of addition according to claim 8, characterized in that: The compressive strength of the large amount of fly ash-based artificial bone is greater than 60MPa, and the test method is as follows: The slurry prepared in step (1-2) was molded into a cubic test block of 10 cm×10 cm×10 cm, and after curing according to step (1-4), its compressive strength was tested.